ASTM designation D3049-89 : Standard test method for synthetic anionic ingredient by cationic titration. (West Conshohocken (Pa.) : ASTM International)
1.1 This test method covers the determination of the amount of synthetic anionic ingredient in a surfactant by direct titration with a standardized cationic reagent. The test method is a simple and convenient means for the quantitative estimation of the anionic material. The end point is detected by the transfer of a colored complex from an organic solvent phase to an aqueous phase. The colored complex is formed by the addition of a solution of dye to a solution of the anionic surfactant. This complex is soluble in the organic-solvent phase and insoluble in the aqueous phase. When this solution is titrated with a standardized solution of a cationic reagent, the dye is displaced from the colored complex and, being water-soluble, migrates to the aqueous phase. Therefore, a cationic titrating solution that has been standardized against a characterized anionic agent can be used to analyze for other anionics of known molecular mass. 1.2 This test method is applicable to alkylaryl sulfonates, alkyl sulfonates, alkyl sulfates and hydroxy-sulfates, alkyl- phenol- and fatty alcohol ethoxy-sulfates and dialkylsulfo- succinates. It applies to active materials containing one hydrophilic group per molecule. 1.3 The analytical procedures appear in the following order: Sections Reagents 6 Primary Standard 8 Purity 8.2 Alcohols 8.3 Free Acid or Alkali 8.4 Preparation of Mixed Indicator Solution 9 Preparation of Hyamine Solution 10 Standardization of Hyamine Solution 11 General Procedure for Anionic-Active Material 12
Keywords: Normen